Association between the PLTP rs4810479 SNP and Serum Lipid Traits in the Chinese Maonan and Han Populations - Fen-Han Zhang; Rui-Xing Yin; Li-Mei Yao; Wei-Xiong Lin; Jin-Zhen Wu; De-Zhai Yang (Genetics Research)
The association between the phospholipid transfer protein (PLTP) gene rs4810479 single-nucleotide polymorphism (SNP) and serum lipid levels is largely unknown. This investigation aimed to evaluate the relationship between the PLTP rs4810479 SNP, several environmental risk factors, and serum lipid parameters in the Chinese Maonan and Han nationalities. Polymerase chain reaction-restriction fragment length polymorphism, gel electrophoresis, and direct sequencing were employed to determine the PLTP rs4810479 genotypes in 633 Maonan and 646 Han participants. The frequencies of CC, CT, and TT genotypes and the C allele were different between Maonan and Han groups (29.07%, 53.08%, 17.85%, and 55.61% vs. 35.60%, 49.70%, 14.70%, and 60.45%, respectively, P<0.05). The C allele carriers in the Maonan group had higher high-density lipoprotein cholesterol levels than the C allele noncarriers, but this finding was only found in Maonan males but not in females. The C allele carriers in Han males had lower total cholesterol and low-density lipoprotein cholesterol levels than the C allele noncarriers. Serum lipid profiles were also affected by several traditional cardiovascular risk factors in both populations. There might be an ethnic- and/or sex-specific association between the PLTP rs4810479 SNP and serum lipid traits.